Diagnostic value of β-N-acetyl-D-glucosaminidase and endoglin as molecular markers in postmenopausal women with urinary bladder neoplasms - Różański, Waldemar; Lipiński, Marek; Woźniak, Paweł; Forma, Ewa; Krześlak, Anna; Bernaciak, Magdalena; Blewniewski, Mariusz; Bryś, Magdalena (Menopause Review/Przegląd Menopauzalny, 2011)
The aim of the study was to evaluate the usefulness of mRNA expression of-N-acetyl-D-glucosaminidase (MGEA5) and endoglin (CD105) for bladder cancer diagnosis and disease prognosis in postmenopausal women. Material and methods: Expression of MGEA5 and CD105 in mRNA with PCR real-time method was estimated in a urine specimen from 30 women with diagnosed bladder cancer. The control group consisted of 20 women with negative cancer history and no changes in the urine specimen and ultrasound examination of the bladder. For both estimated genes, cut-off, specificity and sensitivity were estimated. Results and conclusions : At a cut-off value of MGEA5 of 98.3 sensitivity was 85.2% and specificity 95%. Expression of MGEA5 was established in 27 of 30 (90%) urine specimens taken from women with bladder cancer and in 100% (20 of 20) urine specimens from healthy women. Expression of CD105 was characterized by 100% sensitivity and 80% specificity. Cut-off was over 2.0. There was no CD105 expression in women with papillary urothelial neoplasms of low malignant potential (PUNLMP), in contrast to MGEA5 expression. Estimation of expression of both MGEA5 and CD105 in mRNA of urine specimens of postmenopausal women with urinary bladder may be a useful marker of diagnosis and prognosis of bladder carcinoma.